1988
DOI: 10.1093/carcin/9.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic N-acetylation capacity in lung cancer

Abstract: Hepatic N-acetylation phenotype has been suggested to be an important risk factor in the aetiology of bladder cancer. This study explores the N-acetylation capacity of a series of lung cancer cases (126) and two control groups. No overall association of slow or rapid acetylators exists between cancer patients and controls. There is also no difference in the distribution of acetylation phenotypes amongst the histological subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Phenotyping studies have shown no conclusive relationship of the acetylation status with lung cancer risk; rather, they have shown a reduction of the acetylation capacity of lung cancer patients as compared to healthy subjects [67][68][69]. Such an effect may be attributable either to paraneoplastic effects or to an over-representation of defect acetylation alleles in lung cancer patients.…”
Section: Lung Cancermentioning
confidence: 99%
“…Phenotyping studies have shown no conclusive relationship of the acetylation status with lung cancer risk; rather, they have shown a reduction of the acetylation capacity of lung cancer patients as compared to healthy subjects [67][68][69]. Such an effect may be attributable either to paraneoplastic effects or to an over-representation of defect acetylation alleles in lung cancer patients.…”
Section: Lung Cancermentioning
confidence: 99%
“…Studies have been conflicting with regard to the association with lung cancer risk. Most studies report no overall increase in risk with either the slow or fast acetylators (Philip et al, 1988;Martinez et al, 1995;Bouchardy et al, 1998;Saarikoski et al, 2000), whereas a few have reported increased risk with either the slow (Oyama et al, 1997;Seow et al, 1999) or fast acetylator genotype. In the largest study of 1115 lung cancer patients and 1250 controls, no association was found between the NAT2 genotype and lung cancer risk (Zhou et al, 2002b).…”
Section: Carcinogen Metabolismmentioning
confidence: 99%
“…For instance, in the case of lung cancer there are numerous potential contributors, including polycyclic hydrocarbons, aryl and heterocyclic amines, and nitrosamines. Some convincing evidence has been presented for a role of Nacetyltransferase polymorphism in bladder and colon cancers [Philip et al, 1988;d'Errico et al, 1996]. Epidemiological evidence for a role of P450 1A2 (high level) in bladder cancer has been seen but only in combination with N-acetyltransferase [Lang et al, 1994].…”
Section: Significance Of Variabilitymentioning
confidence: 99%